The Paradigm of Disability: A Discussion of Participation of Persons with Disability in Development in Indonesia - Anggraini, Dewi; Anas, Muhamad; Wike, Wike (The Center for Disability Studies and Services Brawijaya University, 2022)
The aim of this literature study is to catch up on the inclusive development issues in the conception of disability perspective and participation of persons with disabilities in the development goals. This topic is in line with global development which targets seek to accommodate the needs of every citizen including persons with disability to be involved in development. The researcher is using a qualitative approach to construct the conceptual discussion between disability conception and the practice of participation. The data were documented and collected from articles of research that have Indonesian context and legislation. The discussion is described in 4 (four) areas of basic development which are education, health, employment, and accessibility.